Waveguide Encoded Lattices (WELs): Slim Polymer Films with Panoramic Fields of View (FOV) and Multiple Imaging Functionality. (5th September 2017) - Hosein, Ian D.; Lin, Hao; Ponte, Matthew R.; Basker, Dinesh K.; Brook, Michael A.; Saravanamuttu, Kalaichelvi
Abstract: When encoded with a 3D network of interconnected and pentadirectional waveguides, an otherwise passive polymer film transforms into an intelligent optical element—a waveguide encoded lattice (WEL)—that combines a panoramic field of view, infinite depth of field and powerful capacity to perform multiple imaging operations such as divergence‐free transmission, focusing, and inversion. The lattices are moreover operable with coherent and incoherent light at all visible wavelengths, both individually (e.g., narrow band sources such as lasers, light‐emitting diodes) and collectively (e.g., incandescent sources). This combination of properties is unprecedented in single‐component films and the WEL structures represent a new class of flexible, slim films that could confer advanced optical functionalities when integrated with light‐based technologies (e.g., solar panels, smart phone cameras, and smart screens) and are amenable to the design and fabrication of new miniaturized optical and optoelectronic devices. Abstract : Encoding a polymer film with a network of waveguides generates an intelligent element that possesses a panoramic field of view, an infinite depth of field, and can focus, invert, and transmit images without divergence. This unprecedented class of slim, flexible films could confer advanced functionalities to light‐based technologies including solar panels, phone cameras and smart screens.